44 Clinical alert upon cervical cancer situation in the metropolitan area of buenos aires: one out of two women dies when diagnosed under 35 years old. (18th September 2019) - Aragona, A; Soderini, A; Moschen, H; Retamozo Caceres, J; Garrido, R
Abstract : Objectives: To analyze our data collected at the referral Cancer Hospital of Buenos Aires City in order to describe demographic and clinical patterns. Methods: Frequency, survival and demography retrospective assessment (2007–2011) of those patients admitted with a diagnosis of invasive cervical cancer. It was understood by the Metropolitan Area of Buenos Aires, the Buenos Aires City together with the 24 districts that surround it. Age, type and histological grade and clinical stage were considered in the analysis analysis. Survival rates (5-year disease-free and cause-specific) was performed using Kaplan-Meier method and Log-Rank test methods. To investigate the independent effect on the survival, function Cox regression was performed. Results: 748 were assessed. 84% resided in the Metropolitan Area of Buenos Aires; 77% were admitted at an advanced stage. Regarding tumor size, 53.6% had tumors >4 cm diameter and 24.2% >6 cm. The lowest rates of disease-free survival and cause-specific survival were observed for tumor sizes >6 cm and the age subgroup <35. Both tumor size and age retained their prognostic value after multivariate analysis adjustment. When focusing in patients under 35 years old, 48% (n=70) died within 5 years following diagnosis with 5-years survival <50%. Conclusions: It is generally accepted that cervical cancer frequency among young women is low, being the most exposed those over 35 years old. Nevertheless, as gynecologic oncologists, we daily accompany young patients to their death. These figures raise a public health alert on young women in the Metropolitan Area of Buenos Aires, which concentrates almost one third of the country population.